PAIN RELIEVED USING EXTRA ANATOMY PATHWAY IN ACUTE INFECTION - Abdurachman, Abdurachman (Indonesian Journal of Tropical and Infectious Disease, 2012)
Acute infection is characterized especially by pain as major complaint of patients. In this following case report, it will be shown thatÂ pain cause of acute infection can be relieved using acupuncture technique. Acupuncture use meridian as extra anatomy pathway.